2015
DOI: 10.2174/1871530314666141128154152
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Telmisartan vs Lisinopril on Blood Pressure in Patients of Metabolic Syndrome

Abstract: Treatment of metabolic patients with telmisartan or lisinopril for the management of hypertension reduced both Systolic blood pressure (SBP) as well as Diastolic blood pressure (DBP) statistically significantly during 12 weeks treatment. However, telmisartan and lisinopril treatment were found effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…PPAR-α expression in the liver is significantly lower in patients with non-alcoholic fatty liver disease or in animal models of long-term high-fat consumption. 13,14 Everett et al showed that the levels of liver associated free fatty acids significantly increased in PPAR-α knockout mouse models due to attenuated lipid metabolism, promoting liver steatosis. 15 These findings suggest that PPAR-α plays an important role in the pathogenesis of lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-α expression in the liver is significantly lower in patients with non-alcoholic fatty liver disease or in animal models of long-term high-fat consumption. 13,14 Everett et al showed that the levels of liver associated free fatty acids significantly increased in PPAR-α knockout mouse models due to attenuated lipid metabolism, promoting liver steatosis. 15 These findings suggest that PPAR-α plays an important role in the pathogenesis of lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Telmisartan has been proven to be effective in reducing blood pressure in Indian patients with hypertension in clinical trials [ 17 , 18 ] as well as a few real-world studies [ 19 , 20 ]. However, the real-world data currently available are either more than a decade old or localized to a single center.…”
Section: Introductionmentioning
confidence: 99%